2018
DOI: 10.1021/acs.inorgchem.7b02964
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alkoxide Initiator, Spin State, and Oxidation State in Ring-Opening Polymerization of ε-Caprolactone Catalyzed by Iron Bis(imino)pyridine Complexes

Abstract: Density functional theory (DFT) is employed to characterize in detail the mechanism for the ring-opening polymerization (ROP) of ε-caprolactone catalyzed by iron alkoxide complexes bearing redox-active bis(imino)pyridine ligands. The combination of iron with the non-innocent bis(imino)pyridine ligand permits comparison of catalytic activity as a function of oxidation state (and overall spin state). The reactivities of aryl oxide versus alkoxide initiators for the ROP of ε-caprolactone are also examined. An exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 88 publications
(85 reference statements)
0
27
0
Order By: Relevance
“…[ 11,12 ] In this concern, steric and electronic effects again influence the catalytic performance of bis(imino)pyridine [NNN] ligands supported transition metal complexes. [ 13,14 ] However, in literature, bis(imino)pyridine [NNN]‐type ligands are scarce, [ 9,10 ] and in this report, we have successfully synthesized bis(imino)pyridine‐type 2,6‐bis(( E )‐1‐phenyl‐2‐(( E )‐3‐phenylallylidene)hydrazinyl)pyridine ligand. This ligand exhibited a strong π‐acidic character due to the presence of extended conjugation in the ligand frame.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…[ 11,12 ] In this concern, steric and electronic effects again influence the catalytic performance of bis(imino)pyridine [NNN] ligands supported transition metal complexes. [ 13,14 ] However, in literature, bis(imino)pyridine [NNN]‐type ligands are scarce, [ 9,10 ] and in this report, we have successfully synthesized bis(imino)pyridine‐type 2,6‐bis(( E )‐1‐phenyl‐2‐(( E )‐3‐phenylallylidene)hydrazinyl)pyridine ligand. This ligand exhibited a strong π‐acidic character due to the presence of extended conjugation in the ligand frame.…”
Section: Introductionmentioning
confidence: 88%
“…[ 7,8 ] Bis(imino)pyridine [NNN] ligands are among the most widely used ancillary ligands in the transition metal chemistry and catalysis. [ 9,10 ] The effectiveness of these ligands is due to their redox non‐innocence (acceptability of 1–3 electrons) facilitating redox transformations in main‐group metal centers. [ 11,12 ] In this concern, steric and electronic effects again influence the catalytic performance of bis(imino)pyridine [NNN] ligands supported transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…However, zero toxicity of iron-based catalysts has been a significant cause for the search of Fe-based polymerization catalysts. Recently, Cramer et al studied εCL ROP catalyzed by bis(imino)pyridine Fe complexes 27 [72] with the use of DFT modeling at the M06-L level [84] Def2-TZVP and Def2-SVP basis sets (for Fe and residue atoms, respectively) [100]. It was found that high-spin species are more Lewis acidic than low-spin intermediates.…”
Section: Coordination Polymerization Of Lactonesmentioning
confidence: 99%
“…Metal complexes studied in DFT modeling of εCL ROP [55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77]. …”
Section: Figures and Schemesmentioning
confidence: 99%
“…[1][2][3] While living polymerization methodologies in conjunction with carefully chosen and timed monomer additions produce well-defined materials (e.g., block copolymers 2 ), the ability to control chain growth with an external stimulus could lead to many advanced structures and architectures with potentially interesting physical properties. These externally controlled polymerization methodologies rely on changes in chemical reactivity upon application of an external stimulus (chemical, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] electrochemical, [18][19][20] photochemical, [21][22][23][24][25][26][27][28][29][30] thermal, [31][32][33] mechanochemical [34][35][36][37] ), which precisely regulates the incorporation of monomers at a growing polymer chain end. In addition to promoting the synthesis of advanced structures and architectures, 30,45 the spatiotemporal control afforded by these externally controlled polymerizations has enabled the development of new lithographic [38][39][40][41]<...>…”
Section: Introductionmentioning
confidence: 99%